2012
DOI: 10.1111/sode.12006
|View full text |Cite
|
Sign up to set email alerts
|

Young Children's Affective Responses to Acceptance and Rejection From Peers: A Computer‐based Task Sensitive to Variation in Temperamental Shyness and Gender

Abstract: This study presents a novel task examining young children’s affective responses to evaluative feedback—specifically, social acceptance and rejection—from peers. We aimed to determine (1) whether young children report their affective responses to hypothetical peer evaluation predictably and consistently, and (2) whether young children’s responses to peer evaluation vary as a function of temperamental shyness and gender. Four- to seven-year-old children (N = 48) sorted pictures of unknown, similar-aged children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 86 publications
0
12
0
Order By: Relevance
“…Furthermore, given that the social difficulties differentiating these temperament groups were more apparent earlier in development, the present findings suggest that intervening with extremely socially hesitant and withdrawn young children could reshape the brain's coding of motivated behavior toward peers. Work that used a variant of the present study's Chatroom Task found that extremely shy 4- to 7-year-old boys showed particular sensitivity to both positive and negative bids of peer evaluation (Howarth, Guyer, & Perez-Edgar, 2013).…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, given that the social difficulties differentiating these temperament groups were more apparent earlier in development, the present findings suggest that intervening with extremely socially hesitant and withdrawn young children could reshape the brain's coding of motivated behavior toward peers. Work that used a variant of the present study's Chatroom Task found that extremely shy 4- to 7-year-old boys showed particular sensitivity to both positive and negative bids of peer evaluation (Howarth, Guyer, & Perez-Edgar, 2013).…”
Section: Discussionmentioning
confidence: 82%
“…Hence, the findings may not generalize to other populations. For example, rejection reactivity may play a different role in children without elevated inattention and hyperactivity as these associations may be different in other children (e.g., temperamentally shy boys are more reactive to rejection than non-shy boys; Howarth, Guyer, & Perez-Edgar, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…The peer evaluation task was adapted from a previously-validated task used with children as young as age 4 years (Howarth, Guyer, & Pérez-Edgar, 2013). In a study visit prior to the physiological reactivity session, participants were told that they would be playing a game to learn how children choose friends in the next study visit.…”
Section: Methodsmentioning
confidence: 99%